Pengaruh Model Pembelajaran Kooperatif Tipe CIRC (Cooperative Integrated Reading and Composition) dan Berpikir Kritis Terhadap Hasil Belajar Menulis Argumentasi - Purlilaiceu Purlilaiceu (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
This research was conducted to obtain accurate data about the application of cooperative learning model of CIRC type and critical thinking ability in writing argumentation in class XI IPA SMA Negeri CMBBS. The result of the research shows that there is a significant difference between students 'argumentation ability of learning by using cooperative learning model of CIRC (Cooverative Integrated Reading and Composition) with students who learn expository method and there is different of students' argumentation ability with high critical thinking ability students who have low critical thinking skills. This research used experimental method with Experiment design by Treatment 2x2. Quantitative data is obtained through writing tests and critical thinking tests. Analysis of data using 2-way ANOVA and processed using SPSS 16.0 program.